Aeroacoustic sound sources around the wheels of a passenger car - A Computational Fluid Dynamics study using steady state models to evaluate main sources of flow noise - Ringwall, Emil (My University, 2017)
When speaking about wheel noise most people think about the contact noise from wheel and road interaction. Previous experimental studies in wind tunnels show there is an apparent aerodynamic noise source near the front wheels. New legislative demands force car manufacturers to reduce the noise emitted and the wheel noise cannot be ignored anymore. The study has used broadband noise source models incorporated into the commercial software Star CCM+ to locate and analyze sources generated by dipoles and quadrupoles within the ow around the wheels of a DrivAer car model. The methods used are the Curle acoustic analogy, to approximate the dipole sources at the surface, Proudman acoustic analogy, to approximate the quadrupoles generated in the turbulent ow and the Lilley method, approximates the turbulent shear ow sources. Four cases have been studied comparing stationary and rotating wheels as well as open and closed rims. All cases studied show signi cant sources of noise at the front wheels and the simulations have shown a clear dependence of both rim geometry and rotation of the wheels. It is shown that wheel rotation gives a signi cant increase in aeroacoustic noise in both dipole and quadrupole sources while geometry dependence only could be noted in the quadrupole sources.
Keywords: Strömningsmekanik och akustik; Grundläggande vetenskaper; Hållbar utveckling; Transport; Fluid Mechanics and Acoustics; Basic Sciences; Sustainable Development; Transport